2011
DOI: 10.1016/j.ijantimicag.2010.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Ganciclovir treatment in children: evidence of subtherapeutic levels

Abstract: Ganciclovir (GCV) is used to treat babies and older children with cytomegalovirusrelated disease. Treatment courses are generally derived from adult studies and there are few data relating to the pharmacokinetics of GCV in children. In adults, low trough GCV levels have been associated with treatment failure and virological resistance. Data regarding suitable drug levels for use in therapeutic drug monitoring (TDM) in the paediatric age group do not currently exist. In this study, anonymised data for all GCV l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…or prevention (q.d.) of CMV . Nevertheless, recent publications have challenged the valganciclovir pediatric dosing algorithm based on BSA/CrCLS, and simulations have suggested that a simple BW‐based dosing regimen of 14–16 mg/kg valganciclovir b.i.d .…”
mentioning
confidence: 99%
“…or prevention (q.d.) of CMV . Nevertheless, recent publications have challenged the valganciclovir pediatric dosing algorithm based on BSA/CrCLS, and simulations have suggested that a simple BW‐based dosing regimen of 14–16 mg/kg valganciclovir b.i.d .…”
mentioning
confidence: 99%
“…There have been very few TDM data of ganciclovir therapy in extremely premature infants [4]. The response to therapy with ganciclovir has been influenced by the interindividual pharmacokinetic variability.…”
Section: Discussionmentioning
confidence: 99%
“…The response to therapy with ganciclovir has been influenced by the interindividual pharmacokinetic variability. Thus, low plasma levels of ganciclovir are associated with therapy failure and also predispose the virus to drug resistance, although optimal therapeutic drug levels have not been well established [4]. Plasma ganciclovir trough levels below 0.6 mg/L are associated with therapy failure during the intravenous ganciclovir administration for CMV retinitis [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem with this approach was highlighted by Veniza et al [142], who showed that out of eight patients with measured ganciclovir concentrations (following oral valganciclovir administration) which exceeded the in vitro IC50 for Epstein Barr Virus (EBV), four of them did not experience viral suppression. This hints at the problem outlined by Luck et al that the target circulating concentration for ganciclovir is often unknown, and further understanding of PKPD relationships is required [143].…”
Section: Infectious Diseasesmentioning
confidence: 99%